Antifungal Activity ofLactobacillus fermentumTe007,Pediococcus pentosaceusTe010,Lactobacillus pentosusG004, andL. paracasiD5 on Selected Foods - Muhialdin B.J.; Hassan Z.; Sadon S.K. (2024)
Indexed by Scopus/WOS